(untitled) (Journal of Pharmaceutical Negative Results, 2022)
In linguistics, the lexical-semantic, structural-semantic features of some terms are explained by their uniqueness. In modern terminology, it is desirable to clarify concepts such as terminological field, terminosphere, and terminological system. Today, technical, scientific and cultural development has created the basis for certain processes, including the discovery of concepts and methods within a certain field, and the continuous creation of a large number of new lexical units.